The Effect of Attitude Toward Entreprenurship Education and Environmental Factors on Continuance of Entrepreneurship Engagement - Bintang Nadhiva Balqis; Keumala Hayati (Yayasan pendidikan dzurriyatul Quran, 2026)
The growing concern over educated unemployment in Indonesia has strengthened the role of entrepreneurship education as an alternative career pathway for university students. Yet many students who successfully initiate ventures during entrepreneurship programs struggle to sustain their entrepreneurial involvement afterward. This study aims to examine how Attitude Toward Entrepreneurship Education (ATEE) and Environmental Factors (EF) influence the Continuance of Entrepreneurship Engagement (CEE) among participants of the Wadhwani Ignite Program at Universitas Lampung. A quantitative approach was applied through a structured questionnaire distributed to 219 valid respondents, followed by validity, reliability, classical assumption testing, and multiple regression analysis. The findings show that both ATEE and EF significantly affect CEE, with EF demonstrating a stronger and more consistent influence. Students reported meaningful learning experiences and increased motivation from the program, yet many discontinued their ventures due to limited access to funding, mentoring gaps, and the absence of long-term institutional support. Descriptive results also reveal a gap between students’ desire to pursue entrepreneurship and their confidence in sustaining the businesses initiated during the program. The regression model explains 30.7% of the variation in CEE, underscoring that while educational attitudes contribute to entrepreneurial persistence, environmental support becomes the decisive factor in sustaining student ventures. These results highlight the need for universities to reinforce entrepreneurial ecosystems beyond classroom instruction.